2013
DOI: 10.1038/sc.2013.143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of T-score discordance between different sites in Iranian patients with spinal cord injury

Abstract: Objectives: The present study was conducted to determine the prevalence of T-score discordance and its risk factors in a group of patients with spinal cord injury in a university teaching hospital in the Iranian capital of Tehran. Methods: This cross-sectional study was conducted on paraplegic men undergoing bone density testing in an outpatient clinic at a hospital in the Iranian capital, Tehran, between March 2011 and 2012. A questionnaire on demographic and anthropometric characteristics, including age, hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…However, it should be pointed out that most subjects included in our study were young males, with nearly 50 % being under 30 years of age, thereby making it difficult to apply these specific criteria (Tscore) and explaining why we have proposed risk BMD thresholds in absolute values. Previous studies have also indicated a marked bone loss and increased incidence of osteoporosis ranging from 21 to 81 % after SCI [2][3][4][5][6][7]. Nevertheless, in these studies, risk factors for osteoporosis development were analyzed long-term after SCI, and consequently, no early cutoff risk values for BMD have been previously proposed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, it should be pointed out that most subjects included in our study were young males, with nearly 50 % being under 30 years of age, thereby making it difficult to apply these specific criteria (Tscore) and explaining why we have proposed risk BMD thresholds in absolute values. Previous studies have also indicated a marked bone loss and increased incidence of osteoporosis ranging from 21 to 81 % after SCI [2][3][4][5][6][7]. Nevertheless, in these studies, risk factors for osteoporosis development were analyzed long-term after SCI, and consequently, no early cutoff risk values for BMD have been previously proposed.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, depending on the characteristics of the patients and the diagnostic criteria, 21 to 81 % of subjects will develop osteoporosis after SCI [2][3][4][5][6][7], with age, gender, timesince-injury, and severity of SCI being risk factors related to osteoporosis development long-term after injury [3,4]. However, in spite of this common complication, the clinical evaluation and therapeutic approach to these patients is clearly insufficient, with several authors describing the frequent absence of preventive antiosteoporotic treatment in this condition [8,9].…”
Section: Introductionmentioning
confidence: 99%